Ultrasonic assisted fermentation for production of xylanase enzymeusing locally isolated strain of Bacilus badius - N., Masngut; P., Rajandran; N. A., Damanhuri (IOP Publishing, 2020)
Ultrasonic assisted fermentation has been shown to improve the fermentation and product yield; however, less attention has been given to the xylanase production via ultrasonic assisted fermentation. The purpose of this study was to investigate the conditions in which ultrasonic has been employed to enhance fermentation reactions of interest to xylanase production. Previously, the xylanase production from locally isolated strain identified as Bacillus Badiuswas successfully carried out at an optimum condition. In this study, xylanase production was further explored by incorporated ultrasonic assisted fermentation. The study was conducted by varying the ultrasonic process parameters including treatment time, amplitude and duty cycle. Within the studied range, the highest xylanase production was 9.21 U/mL at duty cycle of 10 %, amplitude of 2 % and treatment time of 25 min. However, the production was 21 % lower than that the conventional optimized fermentation. This is due to unoptimized condition of the ultrasonic assisted fermentation as compared to the conventional one. Ultrasonication at the best process parameters is an effective and feasible way to enhance xylanase activity. In the future, we are looking forward to optimize the ultrasonic assisted fermentation to maximized xylanase production.